Comparison of pharmacokinetic similarity, immunogenicity, and safety of mepolizumab and BAT2606 in healthy Chinese men in a double-blinded, randomized, single-dose, three-arm parallel-group phase I trial - Li, Cuiyun; Sun, Jixuan; Xu, Jia; Wu, Min; Li, Xiaojiao; Liu, Zhijie; Dong, Qingfeng; Sun, Yu; Ding, Yanhua (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the similarity of BAT2606 and mepolizumab, including pharmacokinetic profiles, immunogenicity, and safety, in healthy Chinese men.MethodsThis randomized, double-blind, parallel three-arm, single-dose Phase I clinical study enrolled 207 subjects. All subjects enrolled in this study were randomly assigned to receive BAT2606 or mepolizumab (European-sourced Nucala [Nucala-EU] and US-sourced Nucala [Nucala-US]) at a 1:1:1 ratio. In total, 206 subjects received a subcutaneous injection of 100 mg of one of the drugs in this study.ResultsThe mean drug concentration–time curves were similar among the three groups. The 90% confidence intervals of the geometric mean ratios of maximum concentration and area under the curve from time 0 to infinity were within 80.00%–125.00%. There were no adverse events leading to study discontinuation or death, no serious adverse events, and no local injection-site reactions. The rates of adverse events and treatment-related adverse events were comparable among the BAT2606 (78.3% and 66.7%, respectively), Nucala-US (76.5% and 64.7%, respectively), and Nucala-EU groups (82.6% and 71.0%, respectively). The majority of treatment-related adverse events were grade 1 or 2 in severity based on Common Terminology Criteria for Adverse Events version 5.0. Anti-drug antibodies (ADAs) were detected in 4 (5.8%), 10 (14.7%), and 10 subjects (14.5%) in the BAT2606, Nucala-US, and Nucala-EU groups, respectively. All subjects with a positive ADA result were negative for neutralizing antibodies.ConclusionBAT2606 injection was pharmacokinetically bioequivalent to Nucala-US and Nucala-EU in healthy Chinese men. BAT2606 was well tolerated, and its overall safety profile was similar to those of Nucala-US and Nucala-EU. BAT2606 had a numerically lower ADA incidence than Nucala-US and Nucala-EU.Clinical Trial Registrationhttps://www.clinicaltrials.gov/study/NCT05576454?term=BAT2606&rank=1.